ANALISIS YURIDIS PENGAWASAN ASIMILASI DAN INTEGRASI BAGI NARAPIDANA DAN ANAK KETIKA PANDEMI COVID-19 (Studi di Balai Pemasyarakatan Kelas I Malang) - Enny Umronah (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2020)
During the Covid-19 pandemic the Government through the Ministry of Law and Human Right Regulation, issued an Assimilation Policy and Integration for Adult and Children Inmate. The implementation of this policy is accompanied by a monitoring device for Inmates who receive the program. Supervision of the implementation of assimilation and integration is carried out by the Rehabilitation center (Bapas), with a supervisory officer called the Social Adviser (PK). The supervision is carried out by observing and assessing the implementation of the service program, coaching and mentoring of the prisoners that are conducted by online. This supervision is a means of preventing and controlling the Covid-19 virus, and so that they do not violate the law again. Supervision that is not carried out optimally can result in violations of the law again by the perpetrators of criminal acts. Especially in a pandemic situation, the repetition of violations of the law is in the public spotlight, because it makes a double impact on the community apart from the pandemic impact. Based on the description above in this Scientific Writing, the writer takes the title